Internal Control Effectiveness of Financial Management In Private Higher Education - Ernawati Ernawati; Imam Agus Faisol (Master of Accounting Universitas Trunojoyo Madura, 2020)
This research investigates internal control effectiveness in supporting financial management of higher education institutions. The object of this research is an Internal Supervisory Unit at a private higher education named